Salpingectomy for Sterilization: Change in Practice in a Large Integrated Health Care System, 2011–2016. Issue 5 (November 2017) - Powell, C. Bethan; Alabaster, Amy; Simmons, Sarah; Garcia, Christine; Martin, Maria; McBride-Allen, Sally; Littell, Ramey D.
Abstract : OBJECTIVE: To evaluate the utilization rate of salpingectomy for cesarean deliveries and postpartum and interval tubal sterilization procedures. METHODS: This is a retrospective cohort study using the electronic medical record to identify women older than 18 years of age undergoing surgical sterilization from June 2011 to May 2016 in an integrated health care system. The primary objective is to describe the change in utilization rate of salpingectomy for tubal sterilization procedures over time and after a systemwide practice recommendation was issued in 2013. Rates of salpingectomy and tubal occlusion were calculated for each of the five 1-year intervals in the study. Secondary outcomes included blood loss, operating time, length of stay, readmission, and emergency department visits. RESULTS: A total of 10, 741 tubal sterilization procedures were identified. There was an increase in salpingectomies from 0.4% (8/1, 938; 95% CI 0.2–0.8) to 35.5% (902/2, 538; 95% CI 33.7–37.4) of tubal sterilization procedures performed over the study period (test for trend, P <.001). Salpingectomy instead of tubal occlusion increased at cesarean delivery from 0.1% (1/1, 141; 95% CI 0.0–0.5) to 9.2% (125/1, 354; 95% CI 7.8–10.9) (test for trend, P <.001); postpartum from 0% (0/124; 95% CI 0.0–3.0) to 4.5% (9/201; 95% CI 2.4–8.3) (test for trend, P =.003); and as an interval (nonpartum) tubal sterilization procedure from 1% (7/673; 95% CI 0.5–2.1) to 78% (768/983; 95% CI 75.4–80.6) (test for trend, P <.001). Median operative minutes was increased from 52 (95% CI 51–52) to 61.5 (95% CI 57–64), from 33 (95% CI 32–34) to 50 (95% CI 35–64), and from 30 (95% CI 29–30) to 33 (95% CI 32–33), respectively, for salpingectomy compared with tubal occlusion at cesarean delivery and postpartum and interval sterilization. Median blood loss was similar for salpingectomy and tubal occlusion at cesarean delivery (660 mL; 95% CI 600–700 mL compared with 700 mL; 95% CI 680–700 mL) and interval sterilization (both 5 mL; 95% CI 5–5 mL) but was more for salpingectomy postpartum (250 mL; 95% CI 200–500 mL compared with 200 mL; 95% CI 200–200 mL). CONCLUSION: There was a significant increase in salpingectomy for sterilization from June 2011 to May 2016. In the final year of the study, salpingectomy accounted for 78% of interval laparoscopic tubal sterilization procedures and 9% of intrapartum and postpartum procedures. Abstract : In a large, integrated health care system, salpingectomy now accounts for 78% of interval laparoscopic tubal sterilization procedures and 9% of intrapartum and postpartum procedures.